Abnormal methylation of spermatozoa induced by benzo(a)pyrene in rats. (July 2019) - Zhang, CM; Sun, ZX; Wang, ZL; Chen, JS; Chang, Z; Wang, Z; Zhu, L; Ma, ZH; Peng, YJ; Xu, ZA; Wang, SQ
Epigenetic mutations caused by pollutants are possibly linked to many diseases. Benzo(a)pyrene (BaP) is one of the most representative air pollutants and has aroused wide concern because of its strong carcinogenicity. The reproductive toxicity induced by BaP has been identified, but little is known about the characteristics of the methylation changes induced by BaP. In this study, a methylated DNA immunoprecipitation sequencing method was used to detect the methylation of sperm DNA of rats exposed to BaP. Compared with the respective genes in normal rats, there were 3227 hypomethylated genes and 828 hypermethylated genes after BaP exposure. Gene ontology enrichment analysis reported that differentially methylated genes (DMGs) were enriched in the localization, single-multicellular organism process and plasma membrane. Kyoto Encyclopedia of Genes and Genomes pathway analysis showed that the DMGs were significantly enriched in the Ras signalling pathway, Rap1 signalling pathway, pancreatic secretion and neuroactive ligand–receptor interaction. DisGeNET disease spectrum analysis showed that DMGs were associated with infertility and certain genetic diseases. Further research needs to be done to explore whether these abnormal methylation are transgenerational.